Cooperação para educação no Mercosul: o programa marca e a retirada unilateral do Brasil do setor educacional do bloco - Pereira, Tamara Lorenzoni (2021)
Guided by neo-institutionalist liberal theory, institutions have the main role of facilitating the cooperation of countries that have an interest in them. This practice of cooperation reduces uncertainties by promoting greater predictability of the countries concerned. Therefore, Brazil’s trajectory in the Southern Common Market stands out for its importance, assiduous participation, and a big tendency to cooperation since the creation of the group. In this way, the Cooperation for Education in Mercosur represents a big part of this dynamic, bringing out the desire of constituent countries for cooperation since the creation of the Mercosur Educational System (SEM). In 2019, however, Brazil leaves unilaterally from SEM, interrupting twenty years of continuous participation. Based on that, the following research investigates the withdrawal of Brazil from Sem, the earliest program of Educational Cooperation of Mercosur, bringing as most important example the MARCA Program. The hypothesis to be tested in this work is that changes in internal policies directly affected the foreign policy of the country. Through the qualitative method, it seeks to identify, over bibliography and documents, how this withdrawal impacts the cooperation inside-group and in MARCA Program.